Beetroot (Beta Vulgaris L.) Extract Acutely Improves Heart Rate Variability Recovery Following Strength Exercise: A Randomized, Double-Blind, Placebo-Controlled Crossover Trial-Pilot Study. (19th May 2021) - Benjamim, Cicero Jonas R.; S. Júnior, Francisco Wellington; de Figueirêdo, Maria Íris L. S.; Benjamim, Cicera Josilânia R.; Cavalcante, Taisy C. Ferro; da Silva, Amanda A. Marcelino; Monteiro, Larissa Raylane L.; Santana, Milana Drumond R.; Garner, David M.; Valenti, Vitor E.
Abstract: Objective: We assessed the acute effect of beetroot extract intake on cardiovascular and autonomic recovery subsequent to strength exercise. Methods: This is a crossover, randomized, double-blind and placebo-controlled trial. We assessed 16 subjects but only 12 healthy male adults completed the two protocols in two randomized days: Beetroot extract (600 mg in capsule) and placebo (600 mg starch in capsule). Beetroot extract or placebo was ingested, the subjects endured 120 minutes seated at rest, followed by a 75% 1RM strength exercise and then remained seated for 60 minutes at rest. Cardiorespiratory parameters, heart rate (HR) variability (HRV) (SDNN, rMSSD, pNN50, SD1, SD2 HF [ms 2 ]) were estimated before, during exercise and during recovery from exercise. Results: ingestion of beetroot extract before exercise: accelerates the recovery of SBP following physical effort; improves HR recovery to baseline resting levels (beetroot protocol: change in ∼62% vs. placebo protocol: change in ∼80%), and intensifies the return of vagal HR control during recovery after exercise. Conclusions: Beetroot extract acutely improved cardiovascular and autonomic recovery after exercise.